Cryo-electron microscopy of HPV16 pseudovirions reveal changes in capsid conformation upon furin cleavage - Marx, Melissa Lauren (Department of Clinical Laboratory Sciences, 2021)
Persistent infection by oncogenic human papillomavirus (HPV) is the primary cause of cervical cancer, a leading cause of cancer deaths in women worldwide. There are no treatments for HPV infection, and although prophylactic vaccines are effective and safe, they are HPV type specific, provide little therapeutic benefit and developing countries often have limited access to these. Therefore, additional measures against HPV infection are urgently needed. Preventing HPV entry into host cells is an attractive option for therapeutic intervention. The HPV capsid is icosahedral and consists of two proteins, L1 and L2, which participate in entry and infection of host cells. During entry, the virus capsid attaches to the cell surface via binding to heparan sulphate proteoglycans (HSPGs). Cleavage of L2 by a host protease, furin, is necessary for infection and is thought to facilitate a conformational change in the virus capsid. Furin cleavage may affect the ability of HPV to bind to sulphated glycoproteins and a HSPG substitute, heparin. Understanding these proposed structural changes may aid in the development of therapeutics targeting virus entry. Here, we directly visualize the conformation changes to HPV16 pseudovirions (HPV16 PsVs) resulting from cleavage of L2 by exogenous furin using cryoelectron microscopy (cryo-EM). At 5 Å resolution, we observed that furin-cleaved HPV16 PsVs capsids display widespread changes in the arrangement of capsomeres relative to uncleaved control virions. This structural change is relevant because heparin has previously been observed to bind to the HPV16 capsid in the canyon surrounding the capsomere at the five-fold icosahedral symmetry axis, but not in other canyons between capsomeres, related by pseudo-symmetry. This suggests that differences in the relative orientations of the surrounding capsomeres to each other either prevent or allow heparin binding. We observed a narrowing of the putative heparin binding site by 0.4 Å after furin cleavage and propose that this change may be responsible for the transfer of HPV from cell-surface HSPGs to the unknown entry receptor(s) by a yet unidentified mechanism.